2009
DOI: 10.1182/blood-2009-06-225706
|View full text |Cite
|
Sign up to set email alerts
|

A linked donor-recipient study to evaluate parvovirus B19 transmission by blood component transfusion

Abstract: Parvovirus B19V infection can be a serious infection for hematology patients with underlying hemolysis or compromised erythropoiesis syndromes. Although case reports of B19V transmission by blood component transfusion (as contrasted to manufactured plasma derivatives) are rare, no studies have systematically determined a rate of transmission to recipients transfused with B19V DNA-positive components. We used a linked donor and recipient repository and a sensitive, quantitative B19V DNA polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
5
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 29 publications
8
62
5
3
Order By: Relevance
“…In our study, the prevalence of B19V DNA in healthy Korean plasmapheresis donors was 0.1%, which was not high compared with that of other countries such as United States (0.83-0.88%), and Germany and Austria (0.27%) [7,15].…”
Section: Discussioncontrasting
confidence: 66%
“…In our study, the prevalence of B19V DNA in healthy Korean plasmapheresis donors was 0.1%, which was not high compared with that of other countries such as United States (0.83-0.88%), and Germany and Austria (0.27%) [7,15].…”
Section: Discussioncontrasting
confidence: 66%
“…In a donor-recipient-linked study, Klein-man et al [4] showed that TT-B19V infections through blood products from donors with lower DNA concentrations (< 10 6 IU/ml B19V-DNA) are uncommon: the amount of infectious B19V is either insufficient or high titers of protective, neutralizing antibodies are existent. Although we have not traced the recipients of our B19V DNA-positive blood products so far, our data endorse at least the last assumption: in samples with B19V DNA of <10 5 IU/ml, more anti-B19V IgG was present (fig.…”
Section: Discussionmentioning
confidence: 99%
“…Infections with B19V are widespread in human populations and usually occur by droplet transmission via the upper respiratory tract. However, B19V is also a common transfusion-transmissible agent, in particular through pooled plasma derivatives [1,2] but also by cellular blood components [3,4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…Given both the reported frequencies of high-titer viremic blood units and seroprevalence rates in the population, the probability of infection by exposure to single blood or blood components units is low [336,337]. Very few case reports describe symptomatic infections, while linked donor-recipient studies indicate that this situation is infrequent and in most cases clinically irrelevant [338]. Single-donor screenings are therefore unjustified in terms of costs; however, high-risk patients with hematological disorders, immune deficiencies or pregnant women would benefit from the availability of dedicated donations, proven to be free from B19V.…”
Section: Screening and Blood Products' Safetymentioning
confidence: 99%